2018
DOI: 10.1002/imhj.21735
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional and Behavioral Problems in Toddlers With Language Delay

Abstract: Toddlers with language delay are at risk for persistent developmental and behavioral difficulties; however, the association between socioemotional/behavior problems and language in young children is not well understood. This study explored socioemotional/behavior problems in a unique sample of toddlers with language delays using a measure developed explicitly for this age group. Toddlers identified by 18 months with receptive and expressive language delay (LD; n = 30) or typical development (TD; n = 61) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…In and externalizing problem score, but not when gender was controlled. Our findings about the positive correlations between vocabulary and SEB Competence (Horwitz et al, 2003;Thurm et al, 2018), and negative correlations between vocabulary and SEB Total and externalizing problems (Horwitz et al, 2003;Manning et al, 2019;Thurm et al, 2018) are in accordance with previous studies. Some of these studies also suggested that between 18 and 24 to 29 months of age, language and social competence have the strongest relations (Horwitz et al, 2003;Thurm et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In and externalizing problem score, but not when gender was controlled. Our findings about the positive correlations between vocabulary and SEB Competence (Horwitz et al, 2003;Thurm et al, 2018), and negative correlations between vocabulary and SEB Total and externalizing problems (Horwitz et al, 2003;Manning et al, 2019;Thurm et al, 2018) are in accordance with previous studies. Some of these studies also suggested that between 18 and 24 to 29 months of age, language and social competence have the strongest relations (Horwitz et al, 2003;Thurm et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings about the positive correlations between vocabulary and SEB Competence (Horwitz et al, 2003;Thurm et al, 2018), and negative correlations between vocabulary and SEB Total and externalizing problems (Horwitz et al, 2003;Manning et al, 2019;Thurm et al, 2018) are in accordance with previous studies. Some of these studies also suggested that between 18 and 24 to 29 months of age, language and social competence have the strongest relations (Horwitz et al, 2003;Thurm et al, 2018). Thurm and her group (2018) reported social competence at 18 and 24 months to be the only aspect of SEB problems and competencies in a clinical concern rate in the language delayed group of children.…”
Section: Discussionsupporting
confidence: 93%
“…Toddlers in the language delay group also demonstrated lower competence scores, including compliance, attention, mastery motivation, imitation/play, empathy, and prosocial peer relations. Although toddlers in the language delay group and the typically developing group differed significantly on all outcome measures, competence was the only domain in which the majority of the language delay group was reported to be in the clinical concern range (Thurm et al, 2018). Similarly, 4-year olds with language impairment were vulnerable to difficulties in temperament/behavioral problem domains, compounding existing risk from poorer language development.…”
Section: Introductionmentioning
confidence: 88%
“…Language delays can further contribute to the development of symptoms/behavior problems, such as inattention-hyperactivity (Petersen et al, 2013;Visser et al, 2017). Thurm et al (2018) found that toddlers identified as having a language delay were more likely to exhibit externalizing problems, internalizing problems, and dysregulation as compared to toddlers with typical language development. Toddlers in the language delay group also demonstrated lower competence scores, including compliance, attention, mastery motivation, imitation/play, empathy, and prosocial peer relations.…”
Section: Introductionmentioning
confidence: 99%
“…В большинстве случаев ЗРР сопровождается другими проблемами и трудностями, которые могут касаться разных сторон жизни детей [6,7,8]. Так, встречаются убедительные данные о сопутствующих нарушениях в мелкой моторике при ЗРР у детей [9].…”
Section: фгбоу во «тюменский государственный медицинский университет»...unclassified